Interaction of imipenem and tigecycline against carbapenem-resistant acinetobacter baumanii: the relativity of synergism - Alfizah, H.; Siti Sarah, O.Z.; Noraziah, M.Z. (Universiti Kebangsaan Malaysia, 2015)
Acinetobacter baumanii is an opportunistic bacterium that causes widespread nosocomial infections and tends to be multi-resistant to most of antibiotics. Tigecycline is a well-known antibiotic that possesses a wide-range of activities and is very active in vitro towards a variety of resistant pathogens, including A. baumanii. The aim of this study was to evaluate the effects of the imipenem and tigecycline combination against carbapenem-resistant A. baumanii (CRAB). The minimal inhibitory concentration (MIC) was determined using the E-test method. The microbroth checkerboard technique was employed to determine the effects of the imipenem and tigecycline interaction by obtaining the fractional inhibitory concentration (FIC) index value. A time kill (TK) study was performed to identify any synergistic effects when both imipenem and tigecycline were used against CRAB strains. The result demonstrated that all A. baumanni strains exhibited imipenem MIC values of 32 μg/mL. The combination of imipenem and tigecycline demonstrated an additive effect (FIC > 0.5-4) against all of the strains and synergistic activity (decrement of > 2 log10 CFU/mL) towards AC 34/07 and AC 32/06 strains. The use of imipenem in combination with tigecycline resulted in a more efficient activity and an increased capability to control CRAB infections. This effect showed potential combination and may be of importance in the development or modification of antimicrobial agents for the treatment of CRAB infections.